Pemanfaatan Media Pop-Up Box dalam Pembelajaran IPS di SMP Bhakti Kudus - Dewi, Maulina Rahma; Nisa, Aisyah Nur Sayidatun (Universitas Negeri Semarang, 2021)
This study aims to: 1) Determine the form of the use of Pop Up Box media in social studies learning at SMP Bhakti Kudus. 2) Knowing the driving and inhibiting factors in the use of Pop Up Box media in the Social Studies learning process at SMP Bhakti Kudus. This study used qualitative research methods. The results of this study indicate that: 1) The use of Pop Up Box media in social studies learning at SMP Bhakti Kudus is carried out in three stages. The first stage, namely the planning stage, the second stage, namely the implementation stage. The last stage is the evaluation stage. 2) The use of Pop Up Box media encountered several supporting and inhibiting factors. The existence of Pop Up Box media can improve the quality of social studies learning. Meanwhile, the inhibiting factors for the use of media are in terms of schools, teachers, and students.